ANTIBACTERIAL EFFICACY OF FICUS CARICA FRUIT AGAINST FOLLICULITIS AND DERMATITIS BACTERIA AND TOXICITY STUDY IN RATS MODEL - Shahlla Umbreen; Farheen Ansari (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The aim of this study was to find the antibacterial activity of Ficus carica fruit against bacteria isolated from dermatitis and folliculitis. Thus the alarming situation of antibacterial resistance can be battled by using secondary metabolites of plants. Ficus carica fruit was collected, identified and authenticated. After washing, drying and grinding, extracts were made in solvents like ethanol, methanol, petroleum ether and acetone. Samples were collected from dermatitis and folliculitis patients, proceeded for characterization and bacterial isolation. The isolates were subjected to extracts by disk diffusion and well diffusion method to analyze ZoI, MIC and MBC. The maximum extract yield was obtained from methanol. Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumonia were isolated. FCFM showed 15 to 16mm ZoI while FCFA and FCFE were observed with 11mm. FCFM was found safe while performing in vitro study on rats. FCFM was found to be the rich source of secondary metabolites and also proven to be the great source of drug for antimicrobial resistant bacteria. It could be used in therapeutic skin formulations to treat skin infections.